Disability and Theatre : A Practical Manual for Inclusion in the Arts - Barton Farcas, Stephanie (London : Taylor and Francis, 2018)
"Disability and Theatre: A Practical Manual for Inclusion in the Arts is a step-by step manual on how to create inclusive theatre, including how and where to find actors, how to publicize productions, run rehearsals, act intricate scenes like fights and battles, work with unions, contracts, and agents, and deal with technical issues. This practical information was born from the author's 16 years of running the first inclusive theatre company in New York City, and is applicable to any performance level: children's theatre, community theatre, regional theatre, touring companies, Broadway, and academic theatre. This book features anecdotal case studies that emphasize problem solving, real-world application, and realistic action plans. A comprehensive Companion Website provides additional guidelines and hands-on worksheets."--Provided by publisher.
chapter 1 Why This Book? -- chapter 2 What Is Inclusion? -- chapter 3 Vocabulary and Perception -- chapter 4 Recruiting and Finding Artists -- chapter 5 Auditions and Callbacks -- chapter 6 Rehearsals -- chapter 7 Blocking and Fight Sequences -- chapter 8 Costumes, Props and Makeup -- chapter 9 Technical Rehearsals and Final Dress -- chapter 10 Public Relations and Marketing -- chapter 11 The Performance Run and Strike -- chapter 12 Technical Crew and Technical Designs -- chapter 13 Academic Training: Assessment and Sustainability -- chapter 14 Assessment and Sustainability in Theatres -- chapter 15 Afterword -- chapter 16 Case Study Outcomes.
Keywords: People with disabilities and the performing arts